Pola Interaksi Edukatif Guru dan Siswa Dalam Meningkatkan Hasil Belajar SKI di MAS PAB Sampali - AlHasy, Dhiva Munya; S, Soiman; Pulungan, Enny Nazrah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Improving SKI Learning Outcomes at MAS PAB Sampali".  The background is student learning outcomes in SKI subjects.  Educative interaction patterns are one activity that can be an alternative for improving student learning outcomes in SKI subjects.  The aim of this research is to determine the educational interaction patterns of teachers and students in improving SKI learning outcomes and to determine the impact of implementing teacher and student educational interaction patterns in improving SKI learning outcomes. This type of research is qualitative research.  The data collection methods used were observation, interviews and documentation.  Data analysis technique namely data reduction, data presentation, and drawing verification conclusions.  The data sources for the research informants were PKM in the curriculum sector, SKI teachers, and representatives of several students at MAS PAB Sampali. The results of this research are that the educational interaction patterns implemented run effectively.  SKI teachers use a one-way pattern in delivering material, a two-way pattern through question and answer interactions, and a three-way pattern with group activities.  Of the three patterns that have been implemented, they can have a positive impact on improving students' SKI learning outcomes, as proven by students who are increasingly active in learning and have in-depth knowledge of the material that has been explained. Students are also said to have fulfilled the three aspects of learning outcomes, namely cognitive, affective,  and psychomotor.